Tour and path planning methods for efficient data gathering using mobile elements. (2016) - Almi'ani, Khaled; Viglas, Anastasios; Libman, Lavy
We consider a well-established model of data gathering in wireless sensor networks (WSNs) that combines mobile elements visiting some of the nodes, and wireless communication from the rest. Since wireless communication impacts the life-time of the network, there is a need to design the mobile element path so that the required communication is minimised, while the path length is bounded in length. Based on the required structure of the tour we investigate two variations of this problem. First, we consider mobile element tours that start and end at a predefined sink. Then we consider the unrestricted case, where the path is not required to return to the predefined sink node. We propose new algorithms that alternate between the path design and the multi-hop wireless communication routes, and iteratively improve the out-come of each phase. We compare the resulting performance of our algorithms with the best known comparable schemes in the literature.